Adults' Preferences for Intrinsically versus Extrinsically Framed Health Messages Tailored According to Stages of Change: Effects on the Intention to Engage in Physical Activity. Issue 1 (13th September 2021) - Pope, J. Paige; Pelletier, Luc G.; Wall, Hayley
Physical activity rates have prevailed as a worldwide health concern. The WHO's Global Action Plan on Physical Activity 2018–2030 articulated the need to test effective communication strategies that deliver information to enhance physical activity behaviors. The Comprehensive Messaging Strategy for Sustained Behavior Change (CMSSBC) is a promising approach that advocates tailoring messages to one's stage of change and framing them intrinsically rather than extrinsically. This study examined adults' decisions to read and engage with physical activity messages aligned with CMSSBC, considering the role of the message frame, stage of change of the message, stage of change of the participant, as well as the participants goal orientation. Participants ( nmale = 91; nfemale = 103) aged 25 to 65 ( x̅ = 39.53; SD = 10.80) completed an online survey including; demographic questions, assessments of their physical activity goals and stage of change, decision to read eight messages, and a follow-up question providing the option to complete a behavior change task embedded within the messages they chose to read. Results indicated that participants were more likely to choose to read a message if it fit their goal orientation, and overall, they were significantly more likely to read intrinsic as opposed to extrinsic messages. Further, findings demonstrated that participants were more likely to complete the optional behavior change activity contained within the message if they had an intrinsic goal orientation. These findings demonstrate that physical activity information should be framed intrinsically and recognizes that one's goal orientation may significantly influence how people respond to messages.